Integrating local ecological services into intergovernmental fiscal transfers: the case of the ICMS-E in Brazil - Irene Ring (UFZ-Umweltforschungszentrum Leipzig-Halle, 2004)
Local conservation efforts are often related to benefits at higher governmental levels. On the one hand, these efforts are strongly connected to local land-use decisions. On the other hand, activities such as sustainable water management or biodiversity conservation are associated with regional, national or even global public goods. Therefore spatial externalities or spillovers exist that if not adequately compensated lead to an underprovision of the public goods and services concerned. This article investigates intergovernmental fiscal transfers as an innovative instrument to compensate local jurisdictions for the ecological goods and services they provide across local boundaries. From a public finance perspective, fiscal transfers are a suitable instrument to internalise spatial externalities. However, most federal states pre-dominantly use this feature for social and economic public functions rather than ecological public functions. This article investigates the case of the ICMS-E that has first been intro-duced by a few states in Brazil during the 1990s. Part of the revenue of this value-added tax is redistributed to the local level based on ecological indicators. In this way, the state level uses fiscal transfers to compensate municipalities for the existence of protected areas and other ecological services provided within their territory. The Brazilian experience illustrates that such fiscal transfers can represent both a compensation for land-use restrictions to be born and an incentive to appreciate and engage in more conservation activities at the local level.
Keywords: 330; Intergovernmental fiscal transfer; spillover effects; ecological services; economic incentives; local conservation benefits; Brazil; Finanzausgleich; Umweltpolitik; Ökologische Raumplanung; Ökonomischer Anreiz; Brasilien